PENGARUH KEPEMIMPINAN, MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI KANTOR KESYAHBANDARAN UTAMA BELAWAN - Ismail Fahmi (JRMB (Jurnal Riset Manajemen & Bisnis), 2020)
The formulation of problem in this research there is influence  of leadership on performace. There is influence  of motivation on  performance. There is  influence organization culture on performance. There is influence leadership, motivation and organization cultue on performance. The purpose of this research is for know influence and analize of   leadership on performace. For know influence and analize influence of motivation on  performance. For know influence and analize influence of organization culture on performance. For know influence and analize influence of leadership, motivation and organization cultue on performance. The sample in this research is 60 employees, with data analysis technique used is descriptive analysis and multiple linear regression analysis. The research result  is leadership variable influence positive and  significant on  performance. Motivation variable influence positive and  significant on  performance. Organization culture variable influence positive and  significant on  performance. Leadership, motivation and organization culture variable influence positive and  significant on  performance